Alkali cation effects on chloride binding of alkali-activated fly ash and metakaolin geopolymers. (November 2020) - Fu, Chuanqing; Ye, Hailong; Zhu, Kaiqi; Fang, Deming; Zhou, Jianbo
Abstract: In this work, the chloride binding capacity and chloride penetration resistance of alkali-activated fly ash and metakaolin geopolymers synthesized with various alkali cation types (i.e., sodium or potassium) and aluminosilicate composition (i.e., combination of metakaolin and low-calcium pulverized fly ash) are studied. The chloride binding isotherms are measured using a modified equilibrium method and the effect of chloride exposure on the mineralogical alteration of geopolymers is studied by means of X-ray diffraction. The results show that the type of alkali cation considerably affects the chloride binding behaviors of metakaolin-fly ash geopolymers, regardless of aluminosilicate composition. In comparison to the potassium-based activator, sodium activator results in higher strength development, stronger chloride binding capacity, and better resistance to chloride penetration. The metakaolin-fly ash geopolymers immobilize chloride ions through both chemisorptions via the formation of chloride-bearing zeolites (e.g., Cl-chabazite) as well as physical adsorption. The dominant role of physical adsorption in binding mechanism suggests that a high proportion of hydroxyl group in the structure of sodium (or potassium)-aluminosilicate-hydrate (i.e., (N, K)-A-S-H) is exchangeable with chloride ions.